2017
DOI: 10.11646/zootaxa.4311.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Description of five new species and re-description of two species of Amblyseius (Acari: Phytoseiidae) from West Bengal, India

Abstract: In this paper five new mite species are described from West Bengal, India—Amblyseius dahliae sp. nov., A. bengalensis sp. nov., A. brachycalyx sp. nov., A. conulus sp. nov., A. parbatabasii sp. nov., and two species are re-described—Amblyseius largoensis (Muma, 1955) and A. herbicolus (Chant, 1959) (Acari: Phytoseiidae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Remarks -The description and measurements of the adult females collected agree with those provided by McMurtry and Moraes (1984) for specimens from South Pacific, by Karmakar et al 2017 for specimens from West Bengal (India) and by Fang et al (2020) for specimens from Vietnam. This species is an important natural enemy of mite pests in China (Wu et al 2009).…”
Section: Amblyseius Largoensis (Muma)supporting
confidence: 68%
“…Remarks -The description and measurements of the adult females collected agree with those provided by McMurtry and Moraes (1984) for specimens from South Pacific, by Karmakar et al 2017 for specimens from West Bengal (India) and by Fang et al (2020) for specimens from Vietnam. This species is an important natural enemy of mite pests in China (Wu et al 2009).…”
Section: Amblyseius Largoensis (Muma)supporting
confidence: 68%
“…A comprehensive report of Indian phytoseiid mites have been provided by Gupta, 2003, later Karmakar andGupta, 2014;Pramanik and Karmakar, 2016;Karmakar et al, 2017 discovered and reported numbers of new species of phytoseiid mites associated with agri-horticultural crops. They stated that phytoseiid mites were most common predators associated with phytophagous mites in the vegetables and are effective biological control agent against T. urticae, T. macfarlanei, P. latus, B. phoenicis and E. orientalis.…”
Section: Research Contentmentioning
confidence: 99%
“…The knowledge of Indian Phytoseiidae is based on several major contributions by Gupta (2003). Recent studies have raised the total number to 243 species belonging to 21 genera in three subfamilies of Phytoseiidae from India (Karmakar and Gupta, 2014;Pramanik and Karmakar, 2016;Karmakar et al, 2017;Karmakar and Bhowmik, 2018;Kar and Karmakar, 2021;Molla et al, 2021;Bhowmik and Karmakar, 2021). So far, there is no consolidated report of predatory mites from vegetable crops (Lahiri et al, 2004;Karmakar and Gupta, 2011) and Haneef and population followed by Typhlodromips syzygii, Euseius ovalis, Paraphytoseius multidentatus, Neoseiulus longispinosus, Neoseiulus pranadae, Euseius alstoniae, Scapulaseius asiaticus, Typhlodromus (Anthoseius) sp.…”
Section: Introductionmentioning
confidence: 99%
“…A. largoensis merupakan spesies tungau familia Phytoseiidae yang tersebar luas dan melimpah, biasanya ditemukan pada tanaman holtikultura, gulma dan berbagai tanaman yang ada di hutan (Karmakar et al, 2017). A. Largoensis adalah predator generalis yang memakan tungau hama, serangga kecil, termasuk memakan serbuk sari (polen).…”
Section: Gambar 2 Amblyseius Largoensisunclassified